Outbreaks associated with treated recreational water — United States, 2000–2014. Issue 7 (6th July 2018) - Hlavsa, Michele C.; Cikesh, Bryanna L.; Roberts, Virginia A.; Kahler, Amy M.; Vigar, Marissa; Hilborn, Elizabeth D.; Wade, Timothy J.; Roellig, Dawn M.; Murphy, Jennifer L.; Xiao, Lihua; Yates, Kirsten M.; Kunz, Jasen M.; et al.
Abstract : This report summarizes trends in outbreaks associated with recreational water use from 2000–2014, which include infections with pathogens of concern for transplant recipients, such as Legionella and Cryptosporidium